Ownership Concentration and Accounting Conservatism: The Moderating Role of Board Independence - Thi Minh Hang Nguyen; Anh Tho To; Thi Huyen Phan; Nhat Phuong Diem Ngo; Thi Thu Hong Ho (Emerging Science Journal, 2023)
The purpose of this study is to examine the moderating effect of board independence on the relationship between ownership concentration and accounting conservatism. Using fixed-effect regressions for a sample of 165 Vietnamese listed companies from 2007 to 2017, the results revealed that the proportion of outstanding shares owned by the largest shareholder is negatively associated with accounting conservatism and board independence plays a moderating role in this relationship. Our results are robust after applying alternative measures of the largest ownership and correcting for potential endogeneity using fixed-effects regression with instrumental variables. Overall, our evidence shows that firms with concentrated ownership should keep a high non-executive ratio to maintain accounting conservatism. In other words, increasing the number of non-executive directors on boards in firms with a substantial proportion of shares held by the largest shareholder is likely to strengthen the information environment, giving financial reporting more credibility.JEL Classification: G30; G32. Doi: 10.28991/ESJ-2023-07-01-07 Full Text: PDF